A Practical and Efficient Method for the Synthesis of Sorafenib and Regorafenib - Prachi, Ramteke; Gill, Manjinder Singh (SynOpen, 2023)
Efficient, practical syntheses of sorafenib and regorafenib have been achieved in a manner that is free from the problems associated with previously reported methods. The process involved preparation of 4-(4-aminophenoxy)-N-methylpicolinamide (sorafenib intermediate) and 4-(4-amino-3-fluorophenoxy)-N-methylpicolinamide (regorafenib intermediate) using only a single base and did not require the use of an inert atmosphere. The reaction of intermediates with phenyl 4-chloro-3-(trifluoromethyl)phenyl carbamate, prepared using water-assisted synthesis of carbamates, was used to install the main urea functionality in these molecules.
Keywords: sorafenib; regorafenib; diphenyl carbonate; unsymmetrical urea; carbamate